Cálculo de Coeficientes de Fluência de Nêutrons para Equivalente de Dose Individual Utilizando o Geant4 - Rosane Moreira Ribeiro; Denison de Souza Santos; Pedro Pacheco de Queiróz Filho; Claudia L. P. Mauricio; Livia Kelli da Silva; Paula Rocha Pessanha (Brazilian Journal of Radiation Sciences, 2015)
Fluence to dose equivalent conversion coefficients provide the basis for the calculation of area and personal monitors.  Recently, the ICRP has started a revision of these coefficients, including new Monte Carlo codes for benchmarking. So far, little information is available about neutron transport below 10 MeV in tissue-equivalent (TE) material performed with Monte Carlo Geant4 code.  The objective of this work is to calculate neutron fluence to personal dose equivalent conversion coefficients, Hp (10)/ϕ, with Geant4 code. The incidence of monoenergetic neutrons was simulated as an expanded and aligned ﬁeld, with energies ranging between thermal neutrons to 10 MeV on the ICRU slab of dimension 30 x 30 x 15 cm3, composed of 76.2% of oxygen, 10.1% of hydrogen, 11.1% of carbon and 2.6% of nitrogen. For all incident energy, a cylindrical sensitive volume is placed at a depth of 10 mm, in the largest surface of the slab (30 x 30 cm2). Physic process are included for neutrons, photons and charged particles, and calculations are made for neutrons and secondary particles which reach the sensitive volume.  Results obtained are thus compared with values published in ICRP 74. Neutron fluence in the sensitive volume was calculated for benchmarking. The Monte Carlo Geant4 code was found to be appropriate to calculate neutron doses at energies below 10 MeV correctly.